BUILDING A NATIONAL IDENTITY: A GUIDE FOR THE YOUNGER GENERATION - Ngadenan, Suprapti Widiasih; Rachman, Reza Aditya (Institut Riset dan Pengembangan Indonesia, 2025)
Civic Education (PKn) has a strategic role in shaping national identity in the midst of a multicultural Indonesian society. This study aims to examine the contribution of PKn in building the national identity of the younger generation, identify challenges in its implementation, and explore effective learning strategies. Through a literature study approach, this study reveals that PKn not only instills an understanding of the rights and obligations of citizens, but also strengthens the values of democracy, tolerance, and nationalism that are the foundation of national unity. However, various challenges are still faced, such as the limitations of teacher training, the lack of relevance of the material to contemporary social conditions, and the disparity in implementation between regions. Therefore, participatory learning strategies, technology integration, and collaboration between schools and communities are important to increase the effectiveness of PKn. These findings confirm that PKn designed in an adaptive and contextual manner can be a powerful means in strengthening national identity in the era of